Previous Article in Journal
Iterated Darboux Transformation for Isothermic Surfaces in Terms of Clifford Numbers
Previous Article in Special Issue
Mean Value of the General Dedekind Sums over Interval $${[1,\frac{q}{p})}$$

Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# On the Recurrence Properties of Narayana’s Cows Sequence

by
Xin Lin
School of Mathematics, Northwest University, Xi’an 710127, Shaanxi, China
Symmetry 2021, 13(1), 149; https://doi.org/10.3390/sym13010149
Submission received: 29 December 2020 / Revised: 14 January 2021 / Accepted: 15 January 2021 / Published: 17 January 2021

## Abstract

:
In this paper, we consider the recurrence properties of two generalized forms of Narayana’s cows sequence. On the one hand, we study Narayana’s cows sequence at negative indices and express it as the linear combination of the sequence at positive indices. On the other hand, we study the convolved Narayana number and obtain a computation formula for it.
MSC:
11B37; 11B83

## 1. Introduction

Narayana’s cows sequence originated from a problem with cows proposed by the Indian mathematician Narayana in the 14th century. In this problem, we suppose that there is one cow in the beginning and that every cow produces one calf each year from the age of 4 years old. Narayana’s cow problem counts the number of calves produced every year [1,2]. This problem appears to be similar to Fibonacci’s rabbit problem. So too do the answers, known as the Narayana sequence and the Fibonacci sequence.
Narayana’s cows sequence (A000930 in [3]) satisfies a third-order recurrence relation:
$G n = G n − 1 + G n − 3 , for n ≥ 3 .$
This has the initial values $G 0 = 0$ and $G 1 = G 2 = G 3 = 1$ [1]. Explicitly, the characteristic equation of $G n$ is:
$x 3 − x 2 − 1 = 0 ,$
and the characteristic roots are:
Then, the Narayana sequence can be obtained by Binet’s formula:
$G n = A α n + B β n + C γ n .$
For $n ∈ Z ≥ 0$, the generating function of the Narayana sequence is:
$g ( x ) = 1 1 − x − x 3 = ∑ n = 0 ∞ G n + 1 x n .$
With the Vieta theorem, we have:
From Formula (2), we obtain:
$G 0 = A + B + C = 0 , G 1 = A α + B β + C γ = 1 , G 2 = A α 2 + B β 2 + C γ 2 = 1 ,$
which implies:
$A = 1 − β − γ ( α − β ) ( α − γ ) , B = 1 − α − γ ( β − α ) ( β − γ ) , C = 1 − α − β ( γ − β ) ( γ − α ) .$
With Formula (4), we can simplify A, B, and C and obtain:
$A = α α 2 − α β − α γ + β γ = α α 2 + 2 β γ = α 2 α 3 + 2$
and
$B = β 2 β 3 + 2 , C = γ 2 γ 3 + 2 .$
The Narayana sequence was originally defined at positive indices. Actually, it can be extended to negative indices by defining:
$G − n = A α n + B β n + C γ n ,$
The following recurrence relation holds for all integral indices.
$G n = G n − 1 + G n − 3 , n ∈ Z .$
Through a simple computation, the first few terms of $G n$ at negative indices can be obtained from Formulas (5) and (6), so that $G − 1 = 0 , G − 2 = 1 , G − 3 = 0 , G − 4 = − 1$, which also satisfies Relation (7).
The Narayana sequence has a close connection to some famous numbers or sequences and plays an important role in cryptography and combinatorics. For instance, it can be seen as the number of compositions of n into parts 1 and 3. For $n ≥ 3$, the Narayana sequence can be expressed as the row sums of Pascal’s triangle with triplicated diagonals, while the Fibonacci number $F n$ is the row sums of Pascal’s triangle with slope diagonals of 45 degrees [3]. Narayana’s sequence has a beautiful distribution pattern, the ratio of whose consecutive terms approximates the supergolden ratio, which is closely related to the golden ratio [2]. Moreover, the Narayana sequence satisfies good cross-correlation and autocorrelation properties, which provide wide applications in data coding, information theory, and cryptography, and especially in multiparty computation [2,4,5]. More research about the Narayana sequence and its applications can be found in [6,7,8].
In this paper, we study two natural generalized forms of the Narayana sequence $G n$ (i.e., ${ G n | n ∈ Z < 0 }$ and ${ g h ( x ) | h ∈ R > 0 }$) and construct the recurrence relation between these generalized forms and $G n$. Many mathematical efforts have been made concerning these two generalizations of the linear recurrence sequence, such as the Fibonacci sequence $F n$ (A000035 in [3]), the Tribonacci sequence $T n$ (A000073 in [3]), the Lucas sequence $L n$ (A000032 in [3]), and so on.
For the first aspect, Falcon [9,10] obtained the connection between $F n$ and $L n$ and their values at negative indices. He proved that for $n ∈ Z ≥ 0$, the following identities hold.
$F − n = ( − 1 ) n + 1 F n and L − n = ( − 1 ) n + 1 L n .$
Halici and Akyuz [11] proposed a series of formulae expressing $F n$ and $L n$ at negative indices as the linear combination of themselves. For example, they obtained that for any integer $n ≥ 0$ and $k ≥ 1$, one has:
where denotes the binomial coefficients. More works about the linear recurrence sequence at negative indices can be seen in [12,13,14,15].
For the second aspect, Kim et al. [16] and Chen and Qi [17] considered the convolved Fibonacci number $F n ( x )$, which is defined by the generating function:
With the combinatorial methods, they expressed the $F n ( x )$ by the linear combination of $F n ( x )$ itself [16] or $L n$ [17].
where $〈 x 〉 0 = 1$ and $〈 x 〉 i = x ( x + 1 ) ( x + 2 ) ⋯ ( x + n − 1 )$. As a corollary of [17], one has the following identity for $k ∈ Z ≥ 0$:
$∑ a 1 + a 2 + ⋯ + a k = n F a 1 F a 2 ⋯ F a k = 1 2 ( k − 1 ) ! 2 ∑ i = 0 n ( − 1 ) i ( k + i − 1 ) ! ( k + n − i − 1 ) ! i ! ( n − i ) ! L n − 2 i .$
Zhou and Chen [18] studied the convolved Tribonacci number $T n ( x )$, defined by:
They obtained:
$T n ( x ) = 1 6 ∑ u + v + w = n 〈 x 〉 u u ! 〈 x 〉 v v ! 〈 x 〉 w w ! ( 3 T w + 1 − u − 2 T w − u − T w − u − 1 ) × ( 3 T w + 1 − v − 2 T w − v − T w − v − 1 ) − 1 6 ∑ u + v + w = n 〈 x 〉 u u ! 〈 x 〉 v v ! 〈 x 〉 w w ! ( 3 T 3 w + 1 − n − 2 T 3 w + n − T 3 w − 1 − n ) .$
In particular, for $k ∈ Z ≥ 0$, [18] obtained the computational formula for:
$∑ a 1 + a 2 + ⋯ + a k = n T a 1 + 1 T a 2 + 1 ⋯ T a k + 1 .$
Other works related to convolved numbers can be found in [19,20,21,22,23,24].
Recently, Professor Tianxin Cai visited Northwest University and gave a talk about a series of linear recurrence sequences and their properties, which incited our interest in this field. There are many recursive identities concerning the Fibonacci, Tribonacci, and Lucas sequences, etc. However, few studies have been conducted regarding the Narayana sequence. Professor Cai proposed an open problem:
Whether and how can the Narayana sequence at negative indices be expressed by the sequence itself at positive indices?
Inspired by the question above, our work focuses on the new recurrence relations around the Narayana sequence. On the one hand, we study the recursive properties of the Narayana sequence at negative indices. For $n ∈ Z$, we express $G − n$ as the linear combination of $G n$. On the other hand, we consider the convolved Narayana number $G n + 1 ( h )$ defined as:
When $h = 1$, $G n + 1 ( h )$ becomes the Narayana number $G n + 1$. We propose a computation formula for $G n + 1 ( h )$ involved with $G n + 1$. As a corollary, we obtain an identity between $G n + 1 ( h )$ and $G n + 1$.
Our main results are presented as follows.
Theorem 1.
For $n ∈ Z$, we have:
$G − n = G 2 n − 3 G n G n + 1 + 2 G n 2 .$
Theorem 1 solves Professor Cai’s problem completely. It illustrates the connection between the Narayana sequence at the positive index and the negative index. By Theorem 1, we obtain the recurrence property of the sequence at the negative index, which deepens our knowledge of the nature of the sequence.
Theorem 2.
Let $h ∈ R > 0$. For $n ∈ Z ≥ 0$. We have:
$G n + 1 ( h ) = 1 6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! × ( 3 G i − k + 1 − 2 G i − k ) ( 3 G j − k + 1 − 2 G j − k ) − 1 6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i + j − 2 k + 1 − 2 G i + j − 2 k ) .$
Theorem 2 gives a computation formula for $G n + 1 ( h )$ involving $G n$. If h is a positive integer, we can deduce the corollary as follows.
Corollary 1.
Let $h ∈ Z > 0$. For $n ∈ Z ≥ 0$. We have:
The formulae in the theorems and corollary above are recursive and computable. To better reflect our results, we calculated some values for the formula in Theorem 1 and Corollary 1; they are listed in Appendix A. The numerical results for $G − n$ and $G n + 1 ( h ) ( h ∈ Z > 0 )$ meet their definitions, which prove our results numerically. The numerical experiments were performed in Mathematica $12.0$.

## 2. Preliminary

To prove our theorems, we propose some lemmas.
Lemma 1.
For $n ∈ Z ≥ 0$, denote:
$T n = α n + β n + γ n , S n = α n β n + α n γ n + β n γ n ,$
where α, β, and γ are as defined in Formula (1). We have $T 0 = 3$, $T 1 = 1$, $T 2 = 1$; $S 0 = 3$, $S 1 = 0$, $S 2 = − 2$; and the following recurrence relation for $n ≥ 3$.
$T n = T n − 1 + T n − 3 , and S n = − S n − 2 + S n − 3 .$
$T n$ and $S n$ satisfy the identity so that:
$2 S n = T n 2 − T 2 n .$
Proof.
With Formula (4), we obtain the initial value of $T n$ and $S n$ so that $T 0 = 3$, $T 1 = 1$, $S 0 = 3$, $S 1 = 0$, and:
$T 2 = ( α + β + γ ) 2 − 2 ( α β + α γ + β γ ) = 1 , S 2 = ( α β + α γ + β γ ) 2 − 2 α β γ ( α + β + γ ) = − 2 .$
For $n ≥ 3$, we have:
and
From the definition of $T n$ and $S n$, we obtain:
$2 S n = α n ( β n + γ n ) + β n ( α n + γ n ) + γ n ( α n + β n ) = T n ( α n + β n + γ n ) − ( α 2 n + β 2 n + γ 2 n ) = T n 2 − T 2 n .$
The proof of Lemma is 1 completed. □
Note: In fact, the index n of sequence $T n$ and $S n$ in Lemma 1 can be defined with $Z$. Since $α β γ = 1$, we have $T n = S − n$ for $n ∈ Z$. With symmetry, it suffices to consider that $n ∈ Z ≥ 0$.
Lemma 2.
For $n ∈ Z ≥ 0$, we have:
$T n = 3 G n + 1 − 2 G n a n d G n = 9 T n + 2 − 3 T n + 1 − 2 T n 31 .$
Proof.
With Formula (5), we have:
$A ( α 3 + 2 ) = α 2 , B ( β 3 + 2 ) = β 2 , C ( γ 3 + 2 ) = γ 2 .$
Then, we obtain the recurrence relation for $α n$, $β n$, and $γ n$:
Summing the formulae above, we obtain:
$T n = ( A α n + 1 + B β n + 1 + C γ n + 1 ) + 2 ( A α n − 2 + B β n − 2 + C γ n − 2 ) = G n + 1 + 2 G n − 2 = 3 G n + 1 − 2 G n .$
Now, we prove the second formula. Denote:
$G n = A α n + B β n + C γ n = α n + 2 α 3 + 2 + β n + 2 β 3 + 2 + γ n + 2 γ 3 + 2 = N n D .$
The nominator $N n$ and denominator D of $G n$ are:
and
With Formula (4), we compute $N n$ and D, so that:
$D = 1 + 16 + 6 + 8 = 31 , N n = 4 T n + 2 + 7 T n − 1 − 2 T n − 4 ,$
This implies that:
$G n = 4 T n + 2 + 7 T n − 1 − 2 T n − 4 31 = 9 T n + 2 − 3 T n + 1 − 2 T n 31 .$
The last equality holds from Formula (9). □
Lemma 3.
For $n ∈ Z ≥ 0$, we have:
$S n = G − n + 3 G − ( n + 2 ) a n d G − n = 6 S n + 2 + 9 S n + 1 + 4 S n 31 .$
Proof.
With Formulas (4) and (5), we have:
$A = α 2 α 3 + 2 = β γ 1 + 2 β 3 γ 3 and A ( 1 + 2 β 3 γ 3 ) = β γ .$
Similar to Formula (12), we obtain:
Combining the formulae above, we express $S n$ by $G n$.
$S n = ( A β n − 1 γ n − 1 + B α n − 1 γ n − 1 + C α n − 1 β n − 1 ) + 2 ( A β n + 2 γ n + 2 + B α n + 2 γ n + 2 + C α n + 2 β n + 2 ) = G − ( n − 1 ) + 2 G − ( n + 2 ) = G − n + 3 G − ( n + 2 ) .$
Now, we prove the second formula. With Formula (6), we have:
$G − n = 1 α n + 1 + 2 α n − 2 + 1 β n + 1 + 2 β n − 2 + 1 γ n + 1 + 2 γ n − 2 = N − n D − n ,$
whose denominator and nominator are:
and
After a simple computation, the last term of the formula above can also be expressed by $S n$.
$α n + 1 β n − 2 + α n + 1 γ n − 2 + α n − 2 β n + 1 + α n − 2 γ n + 1 + β n + 1 γ n − 2 + β n − 2 γ n + 1 = α n − 2 β n − 2 ( α 3 + β 3 ) + α n − 2 γ n − 2 ( α 3 + γ 3 ) + β n − 2 γ n − 2 ( β 3 + γ 3 ) = 4 S n − 2 − α 3 β 3 γ 3 ( α n − 5 β n − 5 + α n − 5 γ n − 5 + β n − 5 γ n − 5 ) = 4 S n − 2 − S n − 5 .$
Then, we have:
$N − n = S n + 1 + 12 S n − 2 − 2 S n − 5 .$
Thus:
$G − n = S n + 1 + 12 S n − 2 − 2 S n − 5 31 = 6 S n + 2 + 9 S n + 1 + 4 S n 31 .$
Lemma 4.
Let $h ∈ R > 0$. For $n ∈ Z ≥ 0$, we have:
$∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! α i β j γ k = 1 6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i − k + 1 − 2 G i − k ) ( 3 G j − k + 1 − 2 G j − k ) − 1 6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i + j − 2 k + 1 − 2 G i + j − 2 k ) .$
Proof.
For any positive integer i, j, and k, we have:
$T i − k T j − k = ( α i − k + β i − k + γ i − k ) ( α j − k + β j − k + γ j − k ) = α i + j − 2 k + β i + j − 2 k + γ i + j − 2 k + α i − k β j − k + α i − k γ j − k + β i − k α j − k + β i − k γ j − k + γ i − k α j − k + γ i − k β j − k .$
Note that: $α i − k β j − k = ( α i − k β j − k ) ( α k β k γ k ) = α i β j γ k$. Then, the formula above can be reduced to:
$T i − k T j − k = α i + j − 2 k + β i + j − 2 k + γ i + j − 2 k + α i β j γ k + α i β k γ j + α j β i γ k + α k β i γ j + α j β k γ i + α k β j γ i .$
From Formula (11), we have:
$∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! T i − k T j − k = ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i − k + 1 − 2 G i − k ) ( 3 G j − k + 1 − 2 G j − k ) .$
With Formulas (11) and (13), we obtain:
$∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! T i − k T j − k = ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i + j − 2 k + 1 − 2 G i + j − 2 k ) + 6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! α i β j γ k .$
Comparing Formulas (14) and (15), we obtain:
$6 ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! α i β j γ k = ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i − k + 1 − 2 G i − k ) ( 3 G j − k + 1 − 2 G j − k ) − ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! ( 3 G i + j − 2 k + 1 − 2 G i + j − 2 k ) .$
This proves Lemma 4. □

## 3. Proof of Theorems

Now, we complete the proof of Theorems.
Proof of Theorem 1.
For $n ≥ 0$, we have:
$G n T n = ( A α n + B β n + C γ n ) ( α n + β n + γ n ) = A α 2 n + B β 2 n + C γ 2 n + ( A + B ) α n β n + ( A + C ) α n γ n + ( B + C ) β n γ n = G 2 n + ( A + B + C ) G − n − G − n = G 2 n − G − n .$
With Lemma 2, we obtain:
$G − n = G 2 n − 3 G n G n + 1 + 2 G n 2 .$
Similarly, for $n < 0$ we have:
$G − n T − n = A α 2 n + B β 2 n + C γ 2 n + ( A + B ) γ n + ( A + C ) β n + ( B + C ) α n = G − 2 n − G n .$
With Lemma 3 and Formula (7), we obtain:
$G n = G − 2 n − G n ( 3 G − n + 1 − 2 G − n ) = G − 2 n − 3 G − n G − n + 1 + 2 G − n 2 .$
This proves Theorem 1. □
Proof of Theorem 2.
Note that the expansion of power series:
$1 ( 1 − x ) h = ∑ n = 0 ∞ 〈 h 〉 n n ! x n , | x | < 1 .$
Decomposing $g h ( x )$, we obtain:
where $α$, $β$, and $γ$ are the roots of the characteristic equation $x 3 − x 2 − 1 = 0$. With Formula (8), we obtain:
$G n + 1 ( h ) = ∑ i + j + k = n 〈 h 〉 i i ! 〈 h 〉 j j ! 〈 h 〉 k k ! α i β j γ k .$
Theorem 2 follows from Lemma 4. □
Proof of Corollary 1.
Let $h ∈ Z > 0$. With Formulas (3) and (8), we have:
Since for $h ∈ Z > 0$ Corollary 1 can be obtained by Theorem 2. □

## 4. Discussion

The main results of this paper propose new recurrence properties of Narayana’s cow sequence in two generalized forms. First, we consider Narayana’s cows sequence $G n$ at negative indices and construct the relationship between the sequence and itself at positive indices. This illustrates the recurrence property of the sequence at the negative index. Meanwhile, we prove that this connection holds for all integers, and not only for positive integers. Our results solve an open problem proposed by Professor Tianxin Cai completely. In addition, we obtain a computable recurrence formula for the convolved Narayana number. As a corollary, we obtain an identity related to $G n$.

## Funding

This research was funded by the National Natural Science Foundation of China (No. 11771351) and Northwest University Doctorate Dissertation of Excellence Funds (No. YYB17002).

## Acknowledgments

The author would like to thank the reviewers and the editors for their very helpful and detailed comments, which have greatly improved the presentation of this paper.

## Conflicts of Interest

The authors declare no conflict of interest.

## Appendix A

To better illustrate the main results, we present numerical experiments for Narayana’s cows sequence at negative indices and the convolved Narayana number for our main results. Some values of Narayana’s cows sequence at both negative and positive indices are listed in Table A1, where $G 0 = 0$.
Table A1. Some values of $G n$.
Table A1. Some values of $G n$.
n$G − n$$G n$n$G − n$$G n$n$G − n$$G n$
10121−26127841−14072,670,964
21122281873424723,914,488
301231927454317405,736,961
4−1224−54402344−18798,407,925
513259589645−126812,322,413
6142673864146361918,059,374
7−2627−6312,66447−61126,467,299
80928−6418,56048−488738,789,712
93132913627,20149423056,849,086
10−21930139,86550427683,316,385
11−32831−20058,42551−9117122,106,097
125413213585,62652−46178,955,183
1316033201125,4915313,393262,271,568
14−88834−335183,91654−9071384,377,665
15412935−66269,54255−13,439563,332,848
16918936536395,0335622,464825,604,416
17−1227737−269578,9495743681,209,982,081
18−540638−602848,49158−35,9031,773,314,929
1921595398051,243,5245918,0962,598,919,345
20−7872403331,822,4736040,2713,808,901,426
Let $h ∈ Z > 0$. For $n ∈ Z ≥ 0$, we have:
$G h ( n + 1 ) = ∑ a 1 + a 2 + ⋯ + a h = n G a 1 + 1 G a 2 + 1 ⋯ G a h + 1 .$
We list some values of $G h ( n + 1 )$ in Table A2.
Table A2. Some values of $G h ( n + 1 )$.
Table A2. Some values of $G h ( n + 1 )$.
$G h ( n + 1 )$h012345678910
n
111123469131928
212361118305081130208
313613275194171303527906
41410245511623446087916403006
51515401002315051065217543208391
61621621684209872220481510,12220,733
717289126671417924278980721,72146,732
The values in Table A1 and Table A2 were computed from Theorem 1 and Corollary 1. It is easy to verify that the values match their definitions completely, which proves our main results numerically.

## References

1. Allouche, J.P.; Johnson, T. Narayana’s cows and delayed morphisms. J. d’Inform. Music. 1996, hal-02986050. Available online: https://hal.archives-ouvertes.fr/hal-02986050 (accessed on 28 December 2020).
2. Narayana_Pandita. Wikipedia. Available online: https://en.wikipedia.org/wiki/Narayana_Pandita_(mathematician) (accessed on 28 December 2020).
3. Sloane, N.J.A. The On-Line Encyclopedia of Integer Sequences. Available online: https://oeis.org (accessed on 16 January 2021).
4. Kak, S. The Piggy Bank Cryptographic Trope. Infocommun. J. 2014, 6, 22–25. [Google Scholar]
5. Kak, S.C.; Chatterjee, A. On Decimal Sequences. IEEE Trans. Inf. Theory 1981, 27, 647–652. [Google Scholar] [CrossRef]
6. Bilgici, G. THE GENERALIZED ORDER-k NARAYANA’S COWS NUMBERS. Math. Slovaca 2016, 66, 795–802. [Google Scholar] [CrossRef]
7. Goy, T. On identities with multinomial coefficients for Fibonacci-Narayana sequence. Ann. Math. Inform. 2018, 49, 75–84. [Google Scholar] [CrossRef]
8. Ramirez, J.L.; Sirvent, V.F. A note on the k-Narayana sequence. Ann. Math. Inform. 2015, 45, 91–105. [Google Scholar]
9. Falcon, S. On the k-Lucas Numbers of Arithmetic Indexes. Appl. Math. 2012, 3, 1202–1206. [Google Scholar] [CrossRef] [Green Version]
10. Falcon, S. On the comples k-Fibonacci numbers. Falcon Cogent Math. 2016, 3, 1–9. [Google Scholar]
11. Halici, S.; Akyuz, Z. Fibonacci and Lucas Sequences at Negative Indices. Konuralp J. Math. 2016, 4, 172–178. [Google Scholar]
12. Boussayoud, A.; Boughaba, S.; Kerada, M. Generating Functions K-Fibonacci and K-Jacobsthal Numbers at Negative Indices. Electron. J. Math. Anal. Appl. 2018, 6, 195–202. [Google Scholar]
13. Boussayoud, A.; Kerada, M.; Harrouche, N. On the k-Lucas Numbers and Lucas Polynomials. Turk. J. Anal. Number Theory 2017, 5, 121–125. [Google Scholar] [CrossRef] [Green Version]
14. Soykan, Y. Summing Formulas For Generalized Tribonacci Numbers. arXiv 2019, arXiv:1910.03490. [Google Scholar] [CrossRef]
15. Koshy, T. Fibonacci and Lucas Numbers with Applications; John Wiley & Sons: Hoboken, NJ, USA, 2011. [Google Scholar]
16. Kim, T.; Dolgy, D.V.; Kim, D.S.; Seo, J.J. Convolved Fibonacci Numbers and Their Applications. Ars Comb. 2017, 135, 119–131. [Google Scholar]
17. Chen, Z.; Qi, L. Some Convolution Formulae Related to the Second-Order Linear Recurrence Sequence. Symmetry 2019, 11, 788. [Google Scholar] [CrossRef] [Green Version]
18. Zhou, S.; Chen, L. Tribonacci Numbers and Some Related Interesting Identities. Symmetry 2019, 11, 1195. [Google Scholar] [CrossRef] [Green Version]
19. Kilic, E. Tribonacci sequences with certain indices and their sums. Ars Comb. 2008, 86, 13–22. [Google Scholar]
20. Agoh, T.; Dilcher, K. Higher-order convolutions for Bernoulli and Euler polynomials. J. Math. Anal. Appl. 2014, 419, 1235–1247. [Google Scholar] [CrossRef]
21. He, Y.; Kim, T. A higher-order convolution for Bernoulli polynomials of the second kind. Appl. Math. Comput. 2018, 324, 51–58. [Google Scholar] [CrossRef]
22. Ma, Y.; Zhang, W. Some Identities Involving Fibonacci Polynomials and Fibonacci Numbers. Mathematics 2018, 6, 334. [Google Scholar] [CrossRef] [Green Version]
23. Falcon, S.; Plaza, A. On k-Fibonacci numbers of arithmetic indexes. Appl. Math. Comput. 2009, 208, 180–185. [Google Scholar] [CrossRef]
24. Kim, T.; Kim, D.S.; Dolgy, D.V.; Kwon, J. Representing Sums of Finite Products of Chebyshev Polynomials of the First Kind and Lucas Polynomials by Chebyshev Polynomials. Mathematics 2019, 7, 26. [Google Scholar] [CrossRef] [Green Version]
 Publisher’s Note: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.

## Share and Cite

MDPI and ACS Style

Lin, X. On the Recurrence Properties of Narayana’s Cows Sequence. Symmetry 2021, 13, 149. https://doi.org/10.3390/sym13010149

AMA Style

Lin X. On the Recurrence Properties of Narayana’s Cows Sequence. Symmetry. 2021; 13(1):149. https://doi.org/10.3390/sym13010149

Chicago/Turabian Style

Lin, Xin. 2021. "On the Recurrence Properties of Narayana’s Cows Sequence" Symmetry 13, no. 1: 149. https://doi.org/10.3390/sym13010149

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.